2016
DOI: 10.1097/brs.0000000000001376
|View full text |Cite
|
Sign up to set email alerts
|

Lower Muscle Mass and Body Fat in Adolescent Idiopathic Scoliosis Are Associated With Abnormal Leptin Bioavailability

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 42 publications
2
52
1
2
Order By: Relevance
“…In participants who had a BMI of <18.5 kg/m 2 , the prevalence of AIS showed a correlation with BMI; the OR increased up to 1.908 in women. Tam et al [15] reported that lower body mass showed a causal association between low BMI and AIS occurrence. Similar results were observed in another study, in which the mean BMI was 18.6 kg/m 2 in AIS and 19.8 kg/m 2 in controls among adolescents [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In participants who had a BMI of <18.5 kg/m 2 , the prevalence of AIS showed a correlation with BMI; the OR increased up to 1.908 in women. Tam et al [15] reported that lower body mass showed a causal association between low BMI and AIS occurrence. Similar results were observed in another study, in which the mean BMI was 18.6 kg/m 2 in AIS and 19.8 kg/m 2 in controls among adolescents [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low body mass index (BMI) has been reported to have greater effects on the prevalence [15] and severity of AIS [16]. The Cobb angle in the AIS population was shown to be negatively correlated with body weight [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have linked relatively high BMI with earlier menarche, and low BMI with delayed menarche [ 34 - 36 ]. Interestingly, low BMI has also been found to be associated with AIS [ 15 , 26 , 37 ], as well as abnormal levels of leptin - a hormone known to play a role in fat regulation and the onset of puberty [ 37 - 39 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition to greater height, girls with scoliosis also usually have lighter body mass than normal. Studies by Brazolino et al (2015) and Tam et al (2016) showed that adolescents with scoliosis had a lower body mass than normal. A 5-year cohort study by Clark et al (2014) has proven the effect of scoliosis on body mass.…”
Section: Discussionmentioning
confidence: 99%